SWOT APPLICATION ON DETERMINING SHIP YARD DEVELOPMENT STRATEGIES: A CASE STUDY - Ikhwan Syahtaria; Sukarno Sukarno; Ali Mashudi; Edy Widodo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
Sea transportation is a major factor connecting the islands of Indonesia which has strategic and important value in supporting the sustainability of the national economy. Along with the government's policy on the sea highway program and the development of the domestic shipping industry, the growth of the commercial fleet, especially vessels, is currently experiencing rapid progress. In supporting the government program and the demand for reparation and procurement of new ships in domestic production, readiness is required from the shipyard. However, the current condition of the shipyard is only able to meet 83% of the demand for new shipbuilding so that the shipyard still needs to be developed in order to improve its capabilities, so that it can meet the needs and be able to carry out its functions in accordance with the progress of shipping technology. In this study discusses the strategy of developing shipbuilding using qualitative descriptive methods and quantitative SWOT analysis. In this case study shipyard development strategy by increasing the ability of shipyards to meet the demands of ship building by increasing supporting facilities and accompanied by increasing the ability of human resources in the mastery of science and technology. Besides also by conducting cooperation with the domestic shipping industry in the procurement of supporting partsKeywords: Shipyard, Maintenence, SWOT Analysis, Developmen Strategy